REM sleep in acutely traumatized individuals and interventions for the secondary prevention of post-traumatic stress disorder. Issue 1 (31st December 2020) - Repantis, Dimitris; Wermuth, Katharina; Tsamitros, Nikolaos; Danker-Hopfe, Heidi; Bublitz, Jan Christoph; Kühn, Simone; Dresler, Martin
ABSTRACT: Increasing evidence supports a close link between REM sleep and the consolidation of emotionally toned memories such as traumatic experiences. In order to investigate the role of sleep for the development of symptoms related to traumatic experiences, beyond experimental models in the laboratory, sleep of acutely traumatised individuals may be examined on the first night after trauma. This might allow us to identify EEG variables predicting the development of posttraumatic stress disorder (PTSD) symptoms, and guide the way to novel sleep interventions to prevent PTSD. Based on our experience, patients' acceptance of polysomnography in the first hours after treatment in an emergency room poses obstacles to such a strategy. Wearable, self-applicable sleep recorders might be an option for the investigation of sleep in the aftermath of trauma. They would considerably decrease the perceived burden for patients and thus increase the likelihood of successful patient recruitment. As one potential sleep intervention, sleep deprivation directly after trauma has been suggested to reduce the consolidation of traumatic memories and hence act as a secondary preventive measure. However, experimental data from sleep deprivation studies in healthy volunteers with the trauma film paradigm have been inconclusive regarding the beneficial or detrimental effects of sleep on traumatic memory processing. Depending on further insights into the role of sleep in traumatic memory consolidation through observational and experimental studies, several options for therapeutic sleep interventions are conceivable: besides behavioural sleep deprivation, selective REM sleep suppression or enhancement by a pharmacological intervention into the serotonergic, noradrenergic or cholinergic systems might provide novel therapeutic options. While REM-modulating drugs have been used with some success for the prevention of PTSD after trauma, they have never been tried before the first night of sleep. In conclusion, more experimental and observational research is needed before sleep interventions are performed in actual trauma victims.